Zebra Cross Batik for Improving Traffic Conduct Safety Behavior for Craders - Aris Budi Sulistyo; Cahya Putra Dinata (Jurnal Teknologi Transportasi dan Logistik, 2020)
Zebra cross is one of the transportation infrastructure used as a crossing for pedestrian who will cross the road. However, pedestrian awareness to cross the road in the zebra cross is still very less. World Health Organization (WHO) data states, 22% of casualty victims are pedestrian. That figure is equivalent to 747 pedestrians killed per day. In order to increase pedestrian traffic safety awareness to cross the road in the zebra cross, Polres Pekalongan City to innovate the making of zebra cross batik. Pekalongan City Police Station, Central Java, will make batik-ornamented zebra cross at 46 points in the local jurisdiction. One of the zebra cross batik is located in Simpang Hayam Wuruk Street square and Jalan Wahid Hasyim. In this study, a study was conducted to determine the degree of influence of zebra cross batik on pedestrian behavior while crossing at Jalan Hayam Wuruk and Jalan Wahid Hasyim. Based on the opportunities and high creativity, should be utilized by making zebra cross batik in an effort to increase awareness of traffic safety behavior on the crossers. The method in this research is research and development. Based on the analysis result, it is found that the increase of awareness of traffic safety behavior on road crossers reaches 60%.